О ТИПИЗАЦИИ И ФОРМАХ ПРОЯВЛЕНИЯ РУСЛОВЫХ ПРОЦЕССОВ НА РАВНИННЫХ РЕКАХ - Чалов Р.С. (My University, 2003)
The notions "channel processes" and "manifestation modes of channel processes" are founded. The channel processes being the complex of phenomena related to interaction between stream and channel, to erosion, transportation and accumulation of sediments, differ from each other at large, medium and small rivers in the plain conditions. It allows classifying processes under the size of the river. Rock channels take a particular place in such classification.
Keywords: 551.435.13